Exclusion clauses and unfair contract terms - Lawson, Richard (Sweet & Maxwell LondonGB, 2005)
Considers how the courts have considered and interpreted exclusion and limitation clauses. Notes how Parliament has enacted a separate set of controls. Looks at the important role and actions of the Office of Fair Trading in the exercise of its statutory functions.